Low-Dose ACTH Stimulation Test in Obesity: A Randomized Dose Assessment - Leonardo G. Mancillas-Adame; Adriana Sánchez-García; Rene Rodriguez-Gutierrez; Camilo Gonzalez-Velazquez; Fernando Javier Lavalle-Gonzalez; Jorge A. Zuñiga-Hernandez; Adriana Gabriela Rios-Ortega; José Gerardo González-González (International Journal of Endocrinology)
Background. The short cosyntropin test is widely used for adrenal insufficiency screening and diagnosis. Lower cosyntropin doses may have greater sensitivity vs. the standard dose in detecting adrenal dysfunction. Obesity and overweight are increasing, impacting the clinical presentation of some diseases. Currently more than 50% of the subjects diagnosed with autoimmune adrenal insufficiency have a BMI greater than 25, and hence individuals living with overweight and obesity are more frequently requiring evaluation of the adrenal cortical function. Fixed-dose cosyntropin stimulation may not be appropriate for individuals with obesity. Objective. The primary objective was to compare cortisol response to a weight-adapted cosyntropin dose vs. a fixed low dose (1 µg) and a more physiologically fixed dose (10 µg). Methods. Twenty individuals with obesity and 20 age-matched healthy controls underwent in a randomized sequence at least one-week apart, to the The short cosyntropin test with three different doses, 0.2 µg/kg of body weight, 1 or 10 µg fixed dose stimuli. The assessment and data analysis were blinded to the individual and the investigator. Results. Cortisol response was reduced in the group with obesity with the 1 µg fixed dose stimuli at 30 minutes (median, IQR) 649.6 µg, 567.3–738.4 µg for the control group vs. 568.6 µg, 528.4–623.13 µg, p=0.04; there was a lower cortisol peak at 60′ in all the three evaluated doses, with a dose-dependent trend. A weight-adapted cosyntropin dose of 0.2 µg in obesity produces a similar response to the one observed in individuals without obesity. The 1 µg ACTH test falls short on stimulating the cortisol adrenal response in individuals with obesity.